Modified Heat-Stable Toxins (hSTa) of Enterotoxigenic Escherichia coli Lose Toxicity but Display Antigenicity after Being Genetically Fused to Heat-Labile Toxoid LT(R192G) - Liu, Mei; Zhang, Chengxian; Mateo, Kristy; Nataro, James P.; Robertson, Donald C.; Zhang, Weiping (My University, 2011)
Enterotoxigenic Escherichia coli (ETEC) strains are a major cause of diarrhea in humans and animals. Heat-stable (STa) and heat-labile (LT) enterotoxins produced by ETEC disrupt fluid homeostasis in host small intestinal epithelial cells and cause fluid and electrolyte hyper-secretion that leads to diarrhea. ETEC strains producing STa or LT are sufficiently virulent to cause diarrhea, therefore STa and LT antigens must be included in ETEC vaccines. However, potent toxicity and poor immunogenicity (of STa) prevent them from being directly applied as vaccine components. While LT toxoids, especially LT(R192G), being used in vaccine development, STa toxoids have not been included. A recent study (IAI, 78:316-325) demonstrated porcine-type STa toxoids [pSTa(P12F) and pSTa(A13Q)] elicited protective anti-STa antibodies after being fused to a porcine-type LT toxoid [pLT(R192G)]. In this study, we substituted the 8th, 9th, 16th, or the 17th amino acid of a human-type STa (hSTa) and generated 28 modified STa peptides. We tested each STa peptide for toxicity and structure integrity, and found nearly all modified STa proteins showed structure alteration and toxicity reduction. Based on structure similarity and toxic activity, three modified STa peptides: STa(E8A), STa(T16Q) and STa(G17S), were selected to construct LT192-STa-toxoid fusions. Constructed fusions were used to immunize mice, and immunized mice developed anti-STa antibodies. Results from this study provide useful information in developing toxoid vaccines against ETEC diarrhea.
Citation: Liu, M.; Zhang, C.; Mateo, K.; Nataro, J.P.; Robertson, D.C.; Zhang, W. Modified Heat-Stable Toxins (hSTa) of Enterotoxigenic Escherichia coli Lose Toxicity but Display Antigenicity after Being Genetically Fused to Heat-Labile Toxoid LT(R192G). Toxins 2011, 3, 1146-1162.
Keywords: Diarrhea; Etec; Lt-Sta Toxoid Fusion; Sta Toxin; Toxoid; Vaccine